THE IMPLEMENTATION OF COOPERATIVE LEARNING METHOD OF NUMBERED HEADS TOGETHER (NHT) TYPE TO IMPROVE STUDENT LEARNING ACTIVITIES ON LEARNING MATHEMATICS - Rahmad Novi Dwi Pradana; Sunaryo Sunaryo (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
This study was conducted because the students learning activities of seventh-grade students in SMP Muhammadiyah 1 Prambanan academic year 2016/2017 in the learning of mathematics are still lacking. This study aims to increase the students' learning activities in mathematics learning by using the cooperative learning model of Numbered Heads Together (NHT) type on students class VII in SMP Muhammadiyah 1 Prambanan on Even Semester in Academic Year 2016/2017. This study is a classroom action research—the setting using VII B class with number 34 students. The study was conducted two cycles by using a cooperative learning model of Numbered Heads Together (NHT) type. Each cycle is consisting of 2 meetings. Methods of data collection using observation, interview, documentation, and triangulation. Instrument analysis using content validity. The analysis used is descriptive qualitative. The results of this study showed that learning by using cooperative learning model Numbered Heads Together (NHT) type can increase student learning activities in learning mathematics on students class VII in SMP Muhammadiyah 1 Prambanan on even Semester in academic year 2016/2017. These things proven from the observation of student learning activities in learning each cycle has increased. The average observation percentage of student learning activity in cycle I is 51,17% with enough criterion, and in the cycle, II increased to 70,88% with good criterion. The results of interviews with students showed a positive response to student learning activities.